(untitled) (Eurasian Medical Research Periodical, 2022)
This study aimed to find out the effect of ultrasound in detected congenital anomalies, and perinatal outcomes and 150 patients were divided into two groups (90 patients diagnosed with ultrasound with an average age of 30.9 ± 5.5 years) (60 cases were a control group with an average age of 29.5 ± 4.2). In this study, information received between January 1, 2019, and December 31, 2020, was used as databases of different hospitals in Iraq, Department of Obstetrics and Gynecology, which maintains a record of all newborns that show one or more congenital anomalies and statistical analysis was performed using IBM SOFT SPSS 22 for Windows, and the final document was prepared with Microsoft Office package. The results that found in this study were Encephalocele 3 (3.3%) for the ultrasound group ،2 (3.3) for the control- Ventriculomegaly for the ultrasound group, 7 (7.8), 4 (6.7) for the control, Anencephaly for 5 (5.5) and over the control group was 1 (1.7), Posterior fossa cyst with 4 (4.4) for the ultrasound patient while for the control group it was 1 (1.7), Hydrops fetalis for ultrasound group 6 (6.7) and 2(3.3%) for the control group